Psicología : Concurso Nacional de Anteproyectos Facultad de Psicología (2007)
Proyectos premiados.
Keywords: DIEGUEZ FRIDMAN ARQUITECTOS & ASOCIADOS; DIEGUEZ, TRISTÁN; FRIDMAN, AXEL; REGUEIRO, ALEJANDRO MANUEL; FRANGELLA, ROBERTO; SARDIN, HORACIO; DEL PUERTO, VALERIA; COLÓN, DIEGO; AZPIAZU-GARCIA GARCIA; GARCÍA GARCÍA, JAVIER; AZPIAZU, GUSTAVO ADOLFO; AGRA-AGRA-LUENZO-IRIBARREN-SALGADO PEREIRA; AGRA, GERARDO RAMÓN; AGRA, MARINA; LUENZO, HUGO FRANCISCO; IRIBARREN, JUAN MARTÍN; SALGADO PEREIRA, RODRIGO ALEJANDRO; CONCURSOS; PREMIOS; ARGENTINA; BUENOS AIRES; ARQUITECTURA EDUCACIONAL; UNIVERSIDADES; PROYECTOS